News 2.0. - Stanik, John (New York ACM, 2005)
Taking a second look at the news so you don't have to
Keywords: General literature; General; Computer systems organization; Computer system implementation; Microcomputers; Portable devices (e.g. laptops, personal digital assistants).; Information systems; Information storage and retrieval; On-line information services; Information interfaces and presentation; Group organization interfaces; Web